2004
DOI: 10.1074/jbc.m313524200
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Stimulatory Factor (USF) Proteins Induce Human TGF-β1 Gene Activation via the Glucose-response Element–1013/–1002 in Mesangial Cells

Abstract: The hyperglycemia-enhanced flux through the hexosamine biosynthetic pathway (HBP) has been implicated in the up-regulated gene expression of transforming growth factor-␤1 (TGF-␤1) in mesangial cells, thus leading to mesangial matrix expansion and diabetic glomerulosclerosis. Since the ؊1013 to ؊1002 region of the TGF-␤1 promoter shows high homology to glucose-response elements (GlRE) formerly described in genes involved in glucose metabolism, we studied the function of the GlRE in the high glucose-induced TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 46 publications
(47 reference statements)
2
63
2
Order By: Relevance
“…Recent studies that evaluated glucose-induced TGF-␤1 production demonstrated a key role for the upstream stimulatory factor family of transcription factors in vitro as well as in vivo (9,10). The causative role of TGF-␤ in stimulating early gene expression of matrix molecules as well as mesangial matrix accumulation is supported by experiments with neutralizing antibodies in streptozotocin-induced diabetic mice and in db/db mice (11,12).…”
mentioning
confidence: 76%
“…Recent studies that evaluated glucose-induced TGF-␤1 production demonstrated a key role for the upstream stimulatory factor family of transcription factors in vitro as well as in vivo (9,10). The causative role of TGF-␤ in stimulating early gene expression of matrix molecules as well as mesangial matrix accumulation is supported by experiments with neutralizing antibodies in streptozotocin-induced diabetic mice and in db/db mice (11,12).…”
mentioning
confidence: 76%
“…In various non-hepatoma cells, glucose has been shown to increase either nuclear USF1 or USF2 or both [32][33][34]. In HepG2 cells, glucose increases predominantly nuclear USF1, and silencing of USF1 but not USF2 abolished the increase in HL promoter activity.…”
Section: Discussionmentioning
confidence: 97%
“…In USF1 a number of polymorphisms have been reported [36,38,40], some of which are associated with unfavourable results in oral glucose and fat tolerance tests [41], increased adipocyte lipolysis [42] and decreased expression of USF target genes in fat biopsies [40]. In nonhepatic cells, glucose has been shown to increase nuclear expression of either USF1 or USF2 [31][32][33][34]. We hypothesised therefore that expression of USF1 or USF2 itself is subject to regulation by glucose.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that USF1 is associated with the familial combined hyperlipidemia and affects the complex lipid phenotype (Pajukanta et al 2004, Coon et al 2005. USF proteins induce human TGF-b1 gene activation via the glucose-response element (Weigert et al 2004). In order to determine whether the genetic variation of the USF transcription factor-binding site in the VEGF promoter region affects VEGF expression in OIR-BN rats, we performed genotyping of USF-binding site SNP allele and measured the retinal VEGF levels and vascular permeability in 97 F2 rats in response to ischemia.…”
Section: Discussionmentioning
confidence: 99%